Pengembangan Media Pembelajaran Spinning Wheel Bermuatan Tri Hita Karana untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas IV Sekolah Dasar Di Gugus II Kintamani - I Kadek Sutrisna; I Made Sedana; Ni Nyoman Lisna Handayani (EDUKASI, 2025)
This study aimed to develop a Spinning Wheel learning media integrated with the local wisdom concept of Tri Hita Karana and to determine its feasibility, practicality, and effectiveness in improving students’ learning outcomes. The research used a Research and Development (R&D) approach with the ADDIE model consisting of analysis, design, development, implementation, and evaluation stages. The participants were 140 fourth-grade students from several elementary schools in Cluster II, Kintamani District, Bali. Data were collected through validation sheets, questionnaires, observations, and pretest–posttest learning outcome tests. Data analysis used Aiken’s V for validity testing, percentage analysis for practicality testing, and a paired sample t-test for effectiveness. The results showed that the developed Spinning Wheel media had very high validity and practicality based on expert, teacher, and student assessments. The effectiveness test also indicated a significant improvement in student learning outcomes, as shown by higher posttest scores compared to pretest scores. Therefore, the media is feasible, practical, and effective for improving elementary students’ IPAS learning outcomes.